2018
DOI: 10.1088/1475-7516/2018/09/025
|View full text |Cite
|
Sign up to set email alerts
|

Does the Hubble constant tension call for new physics?

Abstract: The Λ Cold Dark Matter model (ΛCDM) represents the current standard model in cosmology. Within this, there is a tension between the value of the Hubble constant, H 0 , inferred from local distance indicators and the angular scale of fluctuations in the Cosmic Microwave Background (CMB). We investigate whether the tension is significant enough to warrant new physics in the form of modifying or adding energy components to the standard cosmological model. We find that late time dark energy explanations are slight… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
198
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(204 citation statements)
references
References 94 publications
3
198
1
2
Order By: Relevance
“…We consider three cases: B 1 = 1.0, B 1 = 5.0, and B 1 13.1. The latter model corresponds to a valid cosmology at the level of the background [51,52]. For this model, δ deviates at Infinite branch β 1 β 4 models.…”
Section: )mentioning
confidence: 91%
“…We consider three cases: B 1 = 1.0, B 1 = 5.0, and B 1 13.1. The latter model corresponds to a valid cosmology at the level of the background [51,52]. For this model, δ deviates at Infinite branch β 1 β 4 models.…”
Section: )mentioning
confidence: 91%
“…3, where it can be observed that for small ratios M Z /g the variation in the number of relativistic degrees of freedom of the new species is large (∆N eff 0.3 corresponds to decoupling temperatures T ν R dec 2 GeV) [67,68] and CMB-S4 [69]. ∆N eff = 0.4 represents the extra contribution required to relieve the tension on the inferred H 0 values from high-and low-redshift observations [70,71]. and vice versa.…”
Section: Beyond the Minimal Model: Cosmological And Collider Constraintsmentioning
confidence: 99%
“…Another promising feature is that our model provides a natural unification of early inflation [20], late-time dark energy [1,2], and early (redshift z 3000) dark energy recently proposed to ease the Hubble tension [21][22][23]. The possible unification of early inflation and late-time dark energy has been widely discussed in the literatures (see Refs.…”
Section: Discussionmentioning
confidence: 73%